Testing and assessment procedure for evaluating the competencies of students (on the example of highly qualified personnel training) - Tatyana Nikolaevna Poddubnaya; Anna Andreevna Yurchenko (Вестник Майкопского государственного технологического университета)
The subject of pedagogical discourse in recent years is the rationale for the development and implementation of an effective testing and assessment procedure for evaluating the students' competencies in the educational process of training scientific and pedagogical personnel in post graduate training programs. This is due to the integration of Russia into a single European educational space and implementation of a competency-based approach to education. The research problem consists in developing a testing and assessment procedure for assessing the formation of students' competencies in highly qualified personnel training. The aim of the research is to analyze and generalize the experience of modeling the fund of assessment tools for post graduate students of FSBEI HE “Kuban State University of Physical Culture, Sports and Tourism”. Methods of analysis, synthesis, analogy, generalization, modeling have been used in the research. The results of the study consist in analyzing the types, component composition and content of the training of scientific and pedagogical personnel used postgraduate training programs, funds of assessment tools, the requirements for their development and testing and assessment materials, as well as the examination procedure. Key findings: fundamental didactic principles underlying the development of the FAT have been described, examples of the assessment and criteria scale and the parameters of the expert evaluation of the FAT of the discipline have been given. The materials of the article can be used as the basis for the development of funds of assessment tools and can be applied in the practice of other higher educational institutions.